EVALUATION OF ACUTE TOXICITY AND HYPOLIPIDEMIC EFFECT OF LOWLP-PT DRY EXTRACT IN WHITE MICE - Hà Thanh Hoà; Phạm Quốc Tuấn; Trần Thị Vân Anh; Hà Quang Lợi; Ngô Thị Xuân Thịnh; Hà Hương Lan; Đào Việt Hưng; Nguyễn Thị Minh Diệp; Dương Quốc Toản; Nguyễn Văn Thịnh (Tạp chí Y học Quân sự, 2025)
Objectives: To evaluate the acute toxicity and hypolipidemic effects of the LOWLP-PT dry extract in white mice. Subjects and methods: An experimental study was conducted on white mice to assess the acute toxicity of the LOWLP-PT dry extract according to OECD guidelines (2002, 2022) and the protocol by Do Trung Dam, using gradually increasing oral doses ranging from 500 to 5,000 mg/kg. The hypolipidemic effect was evaluated using a model of endogenous hyperlipidemia in mice induced by Poloxamer-407, at doses of 500 mg/kg and 1,000 mg/kg. Results: To regarding acute toxicity: the LOWLP-PT dry extract was safe at the maximum tested dose of 5,000 mg/kg and no signs of toxicity or mortality were observed in the test animals; the LD₅₀ could not be determined. Regarding the hypolipidemic effect: compared to the disease control group, the LOWLP-PT dry extract significantly reduced total cholesterol (by 22.8% at 500 mg/kg and 30.8% at 1,000 mg/kg) and LDL-C levels (by 26.0% at 500 mg/kg and 27.5% at 1,000 mg/kg), with statistically significant differences (p < 0.05). Triglyceride levels showed a slight decrease, but the effect was not superior to that of the positive control group. HDL-C levels showed no significant differences among the experimental groups (p > 0.05).